Psammoma bodies in cervicovaginal smears - Zreik, Tony (2001)
Objective: To estimate the prevalence of psammoma bodies in routine cervical cytology specimens and describe clinical diagnoses associated with them in pre- and postmenopausal women. Methods: We identified all reports that contained psammoma bodies from a retrospective review of 34,816 cytology reports over 4 consecutive years from the computerized pathology database at Yale New-Haven Medical Center. Slides were reviewed to confirm and qualify psammoma bodies. Medical records of women with psammoma bodies were reviewed and information on follow-up was collected. Results: We identified 18 women with psammoma bodies on their Papanicolaou smears. The median age was 49.5 years (range 17–78 years). Seven of eight postmenopausal women had gynecologic malignancies. Five presented with postmenopausal bleeding and had uterine serous or clear-cell carcinomas. One presented with a pelvic mass that was ovarian serous carcinoma. Another had a serous carcinoma of the fallopian tube with only psammoma bodies on Papanicolaou smears. Only one of the remaining 11 nonmalignant cases was a postmenopausal woman. Conclusion: The prevalence of psammoma bodies in consecutively screened Papanicolaou smears was 18 of 34,816. Psammoma bodies on Papanicolaou smears are ominous in postmenopausal women. Their presence in asymptomatic premenopausal women warrants further evaluation, but not necessarily surgical exploration